RESPIRATORY SURFACE AREA (GILL AREA) OF THE HILLSTREAM FISH GARRA MULLYA (SYKES) - Joseph, G Loviah (Indian Journal of Fisheries, 2011)
Average gill area per unit body weight in Garra mullya is 159.2 mm^/gbody weight. Weight specific gill area is higher in younger groups and becomesalmost a constant in higher body weights. In G. mullya number of secondarylamellae/mm is fairly large. Gill area is correlated to its habitat.